2010
DOI: 10.1213/ane.0b013e3181c30f78
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Placebo-Controlled Trial of Epidural Morphine Analgesia After Vaginal Delivery

Abstract: There was a 78% reduction in analgesic requirements in women given epidural morphine after vaginal delivery compared with placebo for both primiparous and multiparous patients. Women who receive epidural labor analgesia for vaginal deliveries and stay in the hospital for 24 h after delivery may benefit from postpartum administration of epidural morphine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 17 publications
2
3
0
1
Order By: Relevance
“…Khajavi et al, showed that perineal pain were 96.4%, 63%, 25% and 12% in the first, tenth and fortieth and ninetieth day after birth, respectively. 5 Also, Macarthur et al, in the University of Toronto in Canada reported perineal pain 97% during 24 hours after delivery, 10 which is similar to Khajavi et al 5 In the present study, 98% of patients complained perineal pain in the first 24 hours after delivery ranging from 5-49 by McGill pain questionnaire which is similar to the other studies. 5,10 Thus, it seems that patients require more analgesic drugs within the first day after birth.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Khajavi et al, showed that perineal pain were 96.4%, 63%, 25% and 12% in the first, tenth and fortieth and ninetieth day after birth, respectively. 5 Also, Macarthur et al, in the University of Toronto in Canada reported perineal pain 97% during 24 hours after delivery, 10 which is similar to Khajavi et al 5 In the present study, 98% of patients complained perineal pain in the first 24 hours after delivery ranging from 5-49 by McGill pain questionnaire which is similar to the other studies. 5,10 Thus, it seems that patients require more analgesic drugs within the first day after birth.…”
Section: Discussionsupporting
confidence: 89%
“…5 Also, Macarthur et al, in the University of Toronto in Canada reported perineal pain 97% during 24 hours after delivery, 10 which is similar to Khajavi et al 5 In the present study, 98% of patients complained perineal pain in the first 24 hours after delivery ranging from 5-49 by McGill pain questionnaire which is similar to the other studies. 5,10 Thus, it seems that patients require more analgesic drugs within the first day after birth. Regarding to the dose-dependent analgesic effect of chamomile, it seems that the dose used in this study for analgesic in the first 12 hours and the first day after birth was less than the needed dose.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…There is scant previously published data available to allow establishment of norms for opioid utilization after vaginal delivery. Minassian et al 20 reported 76% of women with perineal laceration or episiotomy after vaginal delivery required opioids within first 48 hours, while Macarthur et al 21 reported incidences of opioid use during 24 hours after vaginal delivery of 7% in patients who received epidural morphine, and 32% in those not receiving epidural morphine. Our study highlights that the vast majority of patients undergoing vaginal delivery do not require opioids after discharge home.…”
Section: Discussionmentioning
confidence: 99%
“…La morphine péridurale permettait, dans ce contexte, une réduction d'environ 78 % des besoins analgé-siques par voie orale ou systémique au cours des premières 24h post-partum et facilite ainsi la mobilisation des patientes et leur réhabilitation. De nouvelles études devraient permettre de pouvoir cibler les sous-groupes les plus à risque de douleurs importantes et qui pourrait bénéficier de cette administration précoce de morphine péridurale (extractions instrumentales, lésions périnéales sévères) [61][62][63].…”
Section: Analgésie Multimodale Et Césarienneunclassified